Severe Sepsis with Multiorgan Failure due to Melioidosis: A Lesson to Learn. (9th April 2021) - Warapitiya, Dinuka S; Subasinghe, Shyama; Silva, Rukshanie Frances de; Piyarisi, Dadallage Lalitha; Jayatilleke, Kushlani
Abstract : Introduction . Melioidosis is a bacterial infection caused by a Gram-negative bacillus Burkholderia pseudomallei, prevalent in Southeast Asia and Northern Australia. Sri Lanka is situated in the endemic belt of melioidosis. Melioidosis has a wide spectrum of clinical presentations and results in high mortality rates in severe infection. Case Report . We report a 54-year-old previously healthy Sri Lankan farmer who presented with septicemia following a cut injury to the right leg while working in a paddy field. Initially, he had mild wound sepsis, and later, his condition deteriorated rapidly. The patient required organ support later for cardiovascular instability, acute liver failure, acute kidney injury, acute respiratory distress syndrome, and coagulopathy. The patient's blood culture was negative on the admission day, and the repeated blood culture taken at the ICU was contaminated with a commensal flora initially and later isolated Burkholderia pseudomallei . Although wound swab culture taken on the first day isolated an organism, it took six days to identify it as Burkholderia pseudomallei . The patient succumbed to severe melioidosis leading to a severe sepsis and multiorgan failure in spite of treatment with meropenem. Conclusion . This case report highlights the importance of considering melioidosis as a differential diagnosis when a patient comes with risk factors for melioidosis.